2004
DOI: 10.1160/th04-02-0126
|View full text |Cite
|
Sign up to set email alerts
|

Compartment- and cell-specific expression of coagulation and fibrinolysis factors in the murine lung undergoing inhalational versus intravenous endotoxin application

Abstract: Intraalveolar and intravascular fibrin formation are typical hallmarks of acute inflammatory lung diseases, and may foster subsequent fibroproliferative events. We investigated the regulation and cellular sources of key coagulation and fibrinolysis factors in lungs undergoing compartmentalized challenge with endotoxin (LPS). BALB/c mice received 15 ng LPS either by intravenous injection or by inhalation. Quantitative gene expression analysis (real-time RT-PCR) was performed for tissue factor (TF), TF pathway i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 55 publications
5
43
0
Order By: Relevance
“…The majority of the abnormalities that we previously observed in LTF mice after LPS-mediated injury (2) are recapitulated by absence of TF on the lung epithelium. These findings add to a growing literature showing that coagulation in the airspace is regulated by lung epithelial cells rather than inflammatory cells (3,9,29,31). Our group has previously reported increased levels of TF in pulmonary edema fluid of patients with acute respiratory distress syndrome compared with patients with hydrostatic pulmonary edema (3).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The majority of the abnormalities that we previously observed in LTF mice after LPS-mediated injury (2) are recapitulated by absence of TF on the lung epithelium. These findings add to a growing literature showing that coagulation in the airspace is regulated by lung epithelial cells rather than inflammatory cells (3,9,29,31). Our group has previously reported increased levels of TF in pulmonary edema fluid of patients with acute respiratory distress syndrome compared with patients with hydrostatic pulmonary edema (3).…”
Section: Discussionsupporting
confidence: 65%
“…The cellular sources of TF that drive the protective effects of TF during direct ALI, and the mechanisms of the protective effects of TF in the airspace, are currently unknown. Several previous studies suggested that inflammatory cells, specifically alveolar macrophages, have intense up-regulation of TF protein and activity in LPS models, bleomycin-induced lung injury, and human ALI (8,9,17). However, emerging data point to the alveolar epithelium as a critical mediator of intraalveolar coagulation (3,6,9,18,19).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…50 These findings supported the hypothesis that PAI-1 is a critical regulator of fibrin deposition in the alveolar space in response to ALI. Further support for this theory was gained from animal models of lung injury, including bacterial endotoxin, 51 and bleomycin 52 models of ALI. These studies established PAI-1, its activity and its regulation, as a critical target for therapies treating the family of diseases displaying poor lung function associated with fibrin deposition including ALI, ARDS and COPD.…”
Section: -22mentioning
confidence: 99%